Talak dalam perspektif fikih, gender, dan perlindungan perempuan - Hemnel Fitriawati; Zainuddin Zainuddin (Yinyang: Jurnal Studi Islam Gender dan Anak, 2020)
This study examines divorce in the perspective of fiqh, gender, and protection of women. The background of this research is the emergence of an understanding of some Islamic societies regarding the use of divorce rights in breaking a marriage bond. The assumption that divorce is the husband’s authoritarian right has resulted in the arbitrary treatment of the husband in bringing divorce to his wife. So that it is against gender equality and protection of women. This study aims to clarify about divorce in terms of the perspective of fiqh, gender and women’s protection. This research uses library research with a qualitative form. Data is collected through articles contained in journals, books and other library materials which are then narrated. The results found that divorce in the perspective of fiqh is regulated by verses of the Quran which implies that divorce cannot be used arbitrarily. Divorce in a gender perspective is interpreted as equal rights between a husband and wife in filing for divorce, such as khuluk and fasakh. While divorce in the perspective of protecting women can be known by analyzing the many verses of the Koran that give a signal relating to the protection of women in the case of divorce.